Biotic and abiotic factors promoting the development and proliferation of water hyacinth (eichhornia crassipes (Mart.) Solms-Laub.) in the Wouri Basin (Douala-Cameroon) and environs, with implications for its control - Voukeng, Sonia Nadege Kenfack (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
The Wouri River, situated in the Wouri Basin, is one of the main rivers of the Littoral Region in the city of Douala in Cameroon. It is a source of income and food for the population living around these areas. Since the 1990s, the fishing, transportation, irrigation and sand extraction activities have been impeded by the invasion of aquatic plants, specifically water hyacinth (Eichhornia crassipes [Mart.] Solms-Laubach: Pontederiaceae). Introduced in 1997 to the shore of Lake Chad, water hyacinth has invaded almost 114 ha of the Wouri Basin. Furthermore, Douala, the economic capital of the Cameroon and location for more than 70% of the country's industries, uses the Wouri River and its tributaries to deposit its effluent and waste, which has worsened the problem of water hyacinth. This thesis examined the ecological and socio-economic impacts of water hyacinth in the Wouri Basin and its possible control. An increase in the nutrients in the water has provided water hyacinth with appropriate conditions for its fast growth during both the rainy and dry seasons. The availability of nutrients in these areas is enhanced by the constant, daily tidal fluctuation of water, providing enough water to the plant for easy nutrient uptake. A survey of the impacts of water hyacinth on aquatic plant communities in the Wouri Basin showed that this plant is able to out-compete native species. Assessment of the impact of water hyacinth on the abundance and diversity of plant communities indicated that at some invaded sites, 65% of the vegetation consisted of water hyacinth. Species found in association with water hyacinth with a high level of abundance-dominance were Pistia stratiotes L. (Araceae) (another invader), Commelina benghalensis L. (Commelinaceae) and Echinochloa pyramidalis (Lam.) Hitchc. & Chase (Poaceae). This component of the study also showed that habitats rich in water hyacinth were poor in diversity, while habitats without water hyacinth were rich in diversity, thus raising awareness of the importance of monitoring invasive aquatic weeds along the Wouri Basin, and of implementing correct control management of all invasive aquatic weeds. Communities living along the invaded rivers are well aware of the range of problems caused by the weed; because as the rivers and water bodies used for fishing, transportation, and sand extraction are progressively invaded by the weed, the riparian population is the first to feel the impact. The impact on people has been noticeable, with an increase in diseases, such as malaria, cholera, diarrhoea, typhoid, filariasis, schistosomiasis, scabies and yellow fever increasing the need for a medicine and hospitalization. Economic losses due to the management of invasive aquatic weeds were recorded, and the Ministry of Environment spent an estimated US$1 200 000 between 2010 and 2015 to manage this scourge. In 2016, an amount of US$160 000 was transferred to these regions to manage invasive aquatic weeds, especially water hyacinth, although manual clearing is still the only method used to control this weed. Isolation of fungi from diseased water hyacinth plants in the Wouri Basin revealed several fungal species, most of which have been isolated from water hyacinth species in water bodies elsewhere, which showed a higher diversity during the dry season than during the rainy season. These fungi included Acremonium zonatum (Sawada). W. Gams (Hypocreaceae), Alternaria eichhorniae Nag Raj & Ponnappa (Pleosporaceae), Chaetomium sp., Colletotrichum sp., Curvularia pallescens Boedjin (Pleosporaceae), Curvalaria sp., Epicoccum nigrum Link (Pleosporaceae), Fusarium sp., Pithomyces chartarum fBerk. & M. A. Curtis) M. B. Ellis (Montagnulaceae), to a lesser extent Myrothecium roridum Tode ex Fr. (Incertae sedis) and Nigrospora sp. Although never released in Cameroon, arthropod biological control agents (Neochetina eichhorniae Warner (Coleoptera, Curculionidae) and N. bruchi Hustache (Coleoptera, Curculionidae)) were present, but their populations were relatively low. The slow spread of the insect population was explained by several factors, among them the tidal fluctuation of water, which has an impact on the population growth of the weevils. Whilst adults may be able to survive tidal fluctuations, larvae are severely impacted by them, contributing to the slow success of biological control. In this study, a significant increase in pathogen-induced disease severity and incidence was noted when Neochetina eichhorniae weevils were present, possibly because larvae tunnelling on the petiole created openings for the penetration of fungal spores. This study highlights the negative impacts of water hyacinth, on the environment, people, and thus economy of Cameroon. The presence of biological control agents and pathogens offers Cameroon the possibility of initiating and properly implementing the biological control option, or an integrated management solution, to manage water hyacinth in the Wouri Basin, and in the rest of Cameroon.
Keywords: Uncatalogued